Adaptation of Indonesian Folk Games as A Method to Increase the Interest of German Students in The Kampung Jerman Simulation - Azhari, Dian Rizky (Nusantara Science and Technology Proceedings)
This research is a continuation of the Kampung Jerman simulation research. Kampung Jerman is a massive role-playing simulation, in which there are various places and situations from various professions and themes of daily life that students can play to practice their spontaneous speaking skills in German language. The purpose of this research is to find a supporting game that can add a fun aspect to the Kampung Jerman simulation. It is intended to create a more comfortable condition to reduce the pressure on students during speaking practice. In addition, the use of Indonesian folk games is expected to give the participants a familiar impression and there is no need for complicated explanations on how to play them. Data were collected through questionnaires given to students representing various levels of language ability. The analytical method used is descriptive-qualitative based on the results of the questionnaire. The results of the analysis show that the six new games have a very high pleasant aspect and have a positive effect on the German language skills of beginners. The number of points given by respondents is almost perfect. There were no negative responses to any of the questionnaire statements. In addition, it is assumed that the game can increase respondents' interest in practicing their German language. From their selection of games, it appears that they think games that use more vocabulary and sentence formation are the best way to complete the Kampung Jerman simulation than games that only emphasize the physical aspect.